Investigation of Ultrasonic Assisted Friction Stir Spot Welding of Magnesium Alloy to Aluminum Alloy - Ji, S.D.; Li, Z.W.; Ma, L.; Yue, Y.M.; Gao, S.S. (Проблемы прочности, 2016)
A new welding method: ultrasonic assisted friction stir spot welding (UAFSSW) was put forward in the present study. UAFSSW was successfully applied to weld dissimilar AZ31 Mg alloy and 6061 Al alloy. Results show that for either conventional FSSW or UAFSSW, sound joints are obtained in the configuration of upper Mg alloy and lower Al alloy. Ultrasonic vibration is beneficial to the upward flow of lower aluminum alloy, the increase of the stir zone (SZ) width and the refinement of the grains in the SZ. All cross sections of the Al–Mg joints exhibit the formation of intermetallic compounds (IMC) in the SZ. The crack of the conventional FSSW joint propagates exactly along the interface between the dissimilar materials and presents an inverted “V” morphology. After reaching the highest point of the hook defect, crack of the UAFSSW joint extends to the keyhole, leaving a portion of Mg alloy on the lower sheet. Conventional FSSW joint and UAFSSW joint show different IMC compositions at the faying interface.